Emergent Topological Hall Effect at a Charge‐Transfer Interface. Issue 50 (16th November 2020) - Lim, Zhi Shiuh; Li, Changjian; Huang, Zhen; Chi, Xiao; Zhou, Jun; Zeng, Shengwei; Omar, Ganesh Ji; Feng, Yuan Ping; Rusydi, Andrivo; Pennycook, Stephen John; Venkatesan, Thirumalai; Ariando, Ariando
Abstract: Exploring exotic interface magnetism due to charge transfer and strong spin‐orbit coupling has profound application in the future development of spintronic memory. Here, the emergence and tuning of topological Hall effect (THE) from a CaMnO3 /CaIrO3 /CaMnO3 trilayer structure are studied in detail, which suggests the presence of magnetic Skyrmion‐like bubbles. First, by tilting the magnetic field direction, the evolution of the Hall signal suggests a transformation of Skyrmions into topologically‐trivial stripe domains, consistent with behaviors predicted by micromagnetic simulations. Second, by varying the thickness of CaMnO3, the optimal thicknesses for the THE signal emergence are found, which allow identification of the source of Dzyaloshinskii–Moriya interaction (DMI) and its competition with antiferromagnetic superexchange. Employing high‐resolution transmission electron microscopy, randomly distributed stacking faults are identified only at the bottom interface and may avoid mutual cancellation of DMI. Last, a spin‐transfer torque experiment also reveals a low threshold current density of ≈10 9 A m −2 for initiating the bubbles' motion. This discovery sheds light on a possible strategy for integrating Skyrmions with antiferromagnetic spintronics. Abstract : This work presents the topological Hall effect found in a CaMnO3 /CaIrO3 /CaMnO3 //LaAlO3 (001) heterostructure, which indicates the presence of magnetic Skyrmions entailing the charge‐transfer induced magnetic superexchange. Thickness variations and atomic structure analyses suggest that the Dzyaloshinskii–Moriya interaction originates from the top CaMnO3 /CaIrO3 interface, but is suppressed at the bottom CaIrO3 /CaMnO3 interface due to the presence of stacking faults.